Comparative Study on Solar Collectorâs Configuration for an Ejector-Refrigeration Cycle - Raffles Senjaya; I Made Astina (Institute for Research and Community Services, Institut Teknologi Bandung, 2008)
Solar collectorâs configuration plays important role on solar-powered refrigeration systems to work as heat source for generator . Three types of solar collector consisting of flat plate, evacuated tube, and compound parabolic solar collectors are compared to investigate their performances. The performances consist of the behavior of heat which can be absorbed by the collectors, heat loss from the collectors and outlet temperature of working fluid at several slopes of the solar collectors. The new accurate analysis method of heat transfer is conducted to predict the performance of the solar collectors. The analysis is based on several assumptions, i.e. sky condition at Bandung is clear and not raining from 08.00 until 17.00 and thermal resistance at cover and absorber plate is negligible. The numerical calculation results confirm that performance of the evacuated tubes solar collector at the same operating conditions is higher than the others. For the case of an evacuated-tubes solar collector system with aperture area of 3.5 m2, the maximum heat which can be absorbed is 3992 W for the highest solar intensity of 970 W/m2 at 12.00 with horizontal position of the solar collector. At this condition, the highest outlet temperature of water is 347.15 K with mass flow rate 0.02 kg/s and inlet temperature 298 K.